The Design of Workscapes: A Scoping Study - Rosa de Wolf; Rob Roggema; Steffen Nijhuis; Nico Tillie (Land)
Population growth and urbanization are straining the limited space in the built environment. The business districts take up a great portion of this built space. These districts face climate change hazards and spatial emptiness due to their profit-driven foundation. Sustainable ambitions and strategic locations offer the potential to rethink business districts and integrate them into the living environment. Understanding business districts as potential workscapes, more socio-ecological inclusive business districts, is a new perspective. This research formulates a method to define the spatial quality of business districts through literature review and spatial analysis. A spatial analysis of forty cases in the Netherlands presents a higher spatial quality on more diverse landscapes. This indicates that diversification of the business districts’ landscape from monotone to multitone is needed to enable workscape development. Landscape-driven urbanism is needed to generate this desired level of quality. The research highlights the strategic location of edge-city business districts, situated between urban and rural areas, showing the potential to strengthen the urban-rural relationship. Further research on and by design is needed to enable workscape development.